CREGIS-Q: a GIS tool to support decision making in case of aquifer contamination emergency - Petrangeli,Anna Bruna; Preziosi,Elisabetta; Campopiano,Francesco; Corazza,Angelo; Duro,Andrea (PeerJ Preprints, 2016)
GIS technology has been used for many years in environmental risk analysis due to its capability to focus on the management and analysis of geographic and alphanumeric data to support spatial decision-making (Vairavamoorthy et al, 2007). Especially in emergency management, a DSS (Decision Support System) constitutes an important task to provide quick responses, though not completely exhaustive, to immediately handle a critical scenario and limit the possible damage. In the framework of a collaboration between the Water Research Institute and the National Civil Protection Department, a customized tool called CREGIS (ContaminazioneRisorseEvento-GIS) has been developed in order to facilitate the emergency management of accidental contamination of aquifers and support decision making (Preziosi et al, 2013). The tool is aimed at both national and local authorities in order to improve response capability for a better emergency management. Originally, the tool has been developed programming Python in an ArcGIS environment; but due to the great development and dissemination of open source software, our aim is to replicate the same structure programming Python in a GIS open source environment (QGIS). The review of the tool's code is still in progress. The goal is to make the tool (now named CREGIS-Q) free and accessible to a greater number of people and stakeholders.
Keywords: Decision support system; GIS and Python; aquifer accidental contamination